Kualitas Pelayanan Kesehatan Dalam Meningkatkan Kepuasan Masyarakat di Puskesmas Penebel II Kabupaten Tabanan - Ni Putu Widya Sriani; I Nyoman Gede Widiana (Jurnal Widya Mahavira, 2025)
This study aims to explain the quality of health services in increasing community satisfaction at the Penebel II Health Center, Tabanan Regency. The approach in this study is qualitative descriptive analysis, because the researcher can obtain previously unexpected findings and can represent visible phenomena. From written data and through interviews with informants and sources, it is hoped that they can present the results of the research more clearly and with quality. Through data analysis, it shows that the quality of services at the Penebel II Health Center is good, but there are still a few shortcomings that need to be improved, namely in the field of physical evidence, so that the quality of health services at the Penebel II Health Center is more effective and efficient. The facilities and infrastructure at the Penebel II Health Center are still inadequate, where the facilities and infrastructure for the Patient and Family Waiting Room. In addition, in the field of human resources, it can be said that there is a shortage of medical personnel (doctors). Where from the results of interviews conducted by the researcher, there were patients who complained about the lack of availability of doctors. Furthermore, satisfaction because when the patient is satisfied due to the absence of complaints submitted by the patient about, employees/nurses are diligent in serving the community, employees/nurses are patient in serving the community, employees/nurses are sincere in providing services, Employees/nurses are fair, without discriminating, employees/nurses are open in providing services.